PENGARUH KREATIVITAS DALAM PETA PIKIRAN TERHADAP HASIL BELAJAR SISWA PADA MATERI ALAT-ALAT OPTIK - Cahya Wulandari; Undang Rosidin; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
The aims of the research are to: (1) identify the improvement of students learning outcomes by using mind map and; (2) the creativity influence of mind map to the students learning outcomes at the subject of optical instruments. The research was conducted in the class of X.3 at SMA Negeri 1 Purbolinggo east Lampung, amount of the student have 31 person in the second semester 2012/2013 with optical instrument subject. This research design has use Pre-Experimental Design, and type of that design has One-Group Pretest-Posttest Design, and than the data were analyzed by Paired Sample T Test to determine the improvement of students learning outcomes and than Simple Linear Regression to determine creativity influence of mind map to the students learning outcomes with use SPSS 17.0. The results of the research showed that :(1) There was an significantly average improvement of students learning outcomes by using mind map; (2) there was a positively and linearly significant creativity influence of mind map to the students learning outcomes at the subject of optical instruments.Kata kunci: hasil belajar siswa, kreativitas, peta pikiran